Development of Numerical Literacy Question Instrument based on Computational Thinking for Mathematics Learning - Zafrullah Zafrullah; Syukrul Hamdi; Astri Wahyuni; Rina Safitri; Resky Nuralisa Gunawan; Yoel Istiawanto (STAI Hubbulwathan Duri, 2024)
This study is developmental research that aims to develop a numeracy literacy instrument based on computational thinking in mathematics learning, using the Plomp model to ensure the quality and relevance of the instrument. Selection of respondents using Cluster Random Sampling involving 220 grade 8 students at 5 State Junior High Schools in Bantul Yogyakarta, the instrument was tested for content validity using the Aiken method, resulting in an average validity score of 0.81, indicating that the instrument is valid. Confirmatory Factor Analysis (CFA) results showed that all latent variables had loading factor values above 0.5, these items more accurately represent numerical literacy abilities based on the computational thinking being measured.. Construct Reliability (CR) and Average Variance Extracted (AVE) analysis show that all dimensions meet the criteria, although the Problem Decomposition dimension requires more attention to its indicators because its AVE value is only slightly above the minimum limit. This study is limited to a relatively small number of respondents, so it is necessary to expand the sample coverage to increase the generalizability of the results. This research develops an effective instrument to improve mathematics learning and prepare students for final exams such as the Asesmen Standardisasi Pendidikan Daerah (ASPD) with better numeracy literacy skills.